Isolation and Characterization of Lewis Base Stabilized Monomeric Parent Stibanylboranes. Issue 44 (4th September 2015) - Marquardt, Christian; Hegen, Oliver; Hautmann, Matthias; Balázs, Gábor; Bodensteiner, Michael; Virovets, Alexander V.; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: The synthesis of the Lewis base stabilized monomeric parent compound of stibanylboranes, "H2 SbBH2 ", is reported. Through a salt metathesis route, the silyl‐substituted compounds (Me3 Si)2 SbBH2 ⋅LB (LB=NMe3, NHC Me ) were synthesized as representatives of derivatives with a SbB σ bond. Under very mild conditions, they could be transformed into the target compounds Me3 N⋅H2 BHSbBH2 ⋅NMe3 and H2 SbBH2 ⋅NHC Me, respectively. The products were characterized by X‐ray structure analysis, NMR spectroscopy, IR spectroscopy, and mass spectrometry. DFT calculations give further insight into the stability and bonding of these unique compounds. Abstract : Getting heavier! The monomeric parent compound of the stibanylboranes, "H2 Sb‐BH2 ", which is only stabilized by a Lewis base, was isolated and completely characterized. DFT calculations give further insight into the stability of these unique compounds.